2009
DOI: 10.1080/08916930902831845
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group B2 is secreted by myeloid cells and has mitogenic and chemoattractant activities similar to high mobility group B1

Abstract: High mobility group B box (HMGB) proteins are a family of chromatin proteins made up of two basic DNA binding domains, HMG box A and B, and a C-terminal acidic tail. HMGB have a highly conserved sequence, but different expression pattern: HMGB1 is almost ubiquitous, whereas the others are highly expressed in only a few tissues in adults. We previously demonstrated that HMGB1 is released by necrotic cells and has chemoattractant activity for inflammatory and stem cells, via binding to receptor for advanced glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…In inflamed tissues, however, the protein was additionally present in the cytoplasm, which is probably important for the secretion of HMGB1. Furthermore, Pusterla and coworkers showed that HMGB2 can also be secreted by myeloid cells and, like HMGB1, has chemoattractant activity (61). In line with these observations, we were interested in whether HMGB2 is also detectable in intestinal luminal contents, and we analyzed a small cohort of stool samples from IBD and control patients.…”
Section: Discussionmentioning
confidence: 95%
“…In inflamed tissues, however, the protein was additionally present in the cytoplasm, which is probably important for the secretion of HMGB1. Furthermore, Pusterla and coworkers showed that HMGB2 can also be secreted by myeloid cells and, like HMGB1, has chemoattractant activity (61). In line with these observations, we were interested in whether HMGB2 is also detectable in intestinal luminal contents, and we analyzed a small cohort of stool samples from IBD and control patients.…”
Section: Discussionmentioning
confidence: 95%
“…HMGB1 also has chemotactic activity on monocytes, macrophages, neutrophils and DCs [42], and can promote the progression of many types of cancer cells [43,44]. Although there is one report that shows a proinflammatory effect of HMGB2 released from necrotic cells [45], the cytokine-like function of other HMGB proteins, if any, remains to be clarified.…”
Section: Reviewmentioning
confidence: 96%
“…Furthermore, HMGB1 has been shown to stimulate the migration of smooth muscle cells and fibroblasts, whereas anti-HMGB1 antibodies inhibited the migration of neuroblastoma and glioma cells (31,32). HCC tissues have been shown to overexpress receptors for advanced glycation end products that could relay HMGB signals (33), indicating a potentially important function of HMGBs (34). HMGB2 has been reported to interact with steroid receptors (35), p53 and p73 (27).…”
Section: Discussionmentioning
confidence: 99%